Tingkat Pengetahuan dan Sikap Mahasiswa Mahasiswi Angkatan 2017 terhadap Stretch Marks di Fakultas Kedokteran Universitas Sumatera Utara - Tengku, Nabila Nurhafizha; Jusuf, Nelva Karmila (SCRIPTA SCORE Scientific Medical Journal, 2022)
Background: Stretch marks are atrophy of the skin due to stretching. The prevalence of people who have stretch marks almost reaches 80% of the population. Women and the 5-50 years age group have twice the risk of developing stretch marks. Objectives: To determine the prevalence of students who have stretch marks and to find out the level of knowledge and attitudes towards stretch marks in FK USU 2017 students. Methods: Descriptive research with cross-sectional design. The research population was 253 people and the sampling technique used was non-probability sampling, namely consecutive sampling and obtained a total sample of 155 people. Data collection used an online questionnaire of google form created by researchers who had been tested for validity. Results: The respondents who have stretch marks were 85 people (54.8%). The knowledge level of women, good (96,4%), moderate (3,6%), and men, good (91,7%), moderate (8,3%). The level of women's attitudes were good (55.4%), moderate (44,6%), while men, good (31,9%), moderate (66,7%), and less (1.4%). The level of knowledge for those who have stretch marks were good (95,3%), moderate (4,7%), and who do not have stretch marks were good (92,9%), moderate (7,1%). The level of attitudes with stretch marks were good (49,4%), moderate (50,6%), while without it was good (38,6%), moderate (60%), and less (1,4%). Conclusion: The majority of knowledge of the FK USU 2017 students were good (94,2%) and the majority of attitudes of the FK USU 2017 students were moderate (54,8%). Keywords: attitude, knowledge, online questionnaire, stretch marks Â  Latar Belakang: Stretch marks merupakan penyakit atrofi pada kulit akibat peregangan. Prevalensi orang yang memiliki stretch marks hampir mencapai 80% dari populasi. Wanita dan kelompok usia 5-50 tahun mempunyai risiko dua kali lebih sering terkena stretch marks. Tujuan: Untuk mengetahui prevalensi mahasiswa dan mahasiswi yang memiliki stretch marksdan untuk mengetahui tingkat pengetahuan dan sikap mahasiswa dan mahasiswi terhadap stretch marks. Metode: Penelitian deskriptif dengan rancangan cross-sectional. Populasi penelitian berjumlah 253 orang dan teknik pengambilan sampel yang digunakan berupa non-probability sampling yaitu consecutive sampling dan didapatkan jumlah sampel sebanyak 155 orang. Pengumpulan data dilakukan menggunakan kuesioner online berupa google form yang dibuat oleh peneliti yang sudah dilakukan uji validitas. Hasil: Jumlah responden yang memiliki stretch marks sebanyak 85 orang (54,8%). Tingkat pengetahuan mahasiswi, baik (96,4%), cukup (3,6%), sedangkan pada mahasiswa, baik (91,7%), cukup (8,3%). Tingkat sikap mahasiswi, baik (55,4%), cukup (44,6%), sedangkan pada mahasiswa, baik (31,9%), cukup (66,7%), dan kurang (1,4%). Tingkat pengetahuan responden yang memiliki stretch marks, baik (95,3%), cukup (4,7%), sedangkan responden yang tidak memiliki stretch marks, baik (92,9%), cukup (7,1%). Tingkat sikap responden yang memiliki stretch marks, baik (49,4%), cukup (50,6%), sedangkan responden yang tidak memiliki stretch marks, baik (38,6%), cukup (60%), dan kurang (1,4%). Kesimpulan: Tingkat pengetahuan mahasiswa dan mahasiswi FK USU angkatan 2017 mayoritas baik (94,2%) dan tingkat sikap mahasiswa dan mahasiswi FK USU angkatan 2017 mayoritas cukup (54,8%). Kata Kunci: kuesioner online, pengetahuan, sikap, stretch marks